Tinjauan Sindrom Inflamasi Multisistem pasca COVID-19 pada Anak - Yogi Prawira; Nicodemus Nicodemus (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2022)
Coronavirus disease (COVID-19) caused by infection of severe respiratory syndrome coronavirus 2 (SARS-CoV-2) was first detected in December 2019. Since then, many countries have started reporting a series of cases in children post COVID-19 infection, with various clinical manifestations, i.e: persistent fever, cardiovascular shock, and hyperinflammation similar with Kawasaki disease and/or toxic shock syndrome. The terminology Pediatric Inflammatory Multisystem Syndrome Temporarily Associated with SARS-CoV-2 (PIMS-TS) was given by the Royal College of Paediatrics and Child Health (RCPH), hence commonly known as Multisystem Inflammatory Syndrome in Children (MIS-C) as named by the Centers for Disease Control (CDC) and the World Health Organization (WHO). Multisystem Inflammatory Syndrome in Children has a very wide spectrum of clinical signs and symptoms, with the most common symptoms reported is persistant fever, along with gastrointestinal, cardiovascular and dermatological symptoms. Fever is reported in 97-100% of patients. Gastrointestinal symptoms are the second most common symptom occurring in 70% of patients. Until now, the pathogenesis underlying the occurrence of MIS-C is still unknown. Multisystem Inflammatory Syndrome in Children case management requires multidisciplinary knowledge. Consensus or standard guideline for the management of MIS-C is a work in progress, but in general, the initial management includes intravenous immunoglobulin (IVIG) and corticosteroids.